(untitled) (International Journal of Creative Future and Heritage (TENIAT), 2025)
ABSTRACT This study explores the historical and cultural significance of Royal Embroidery of Manchu, which flourished during the Qing dynasty (1636–1912), particularly under the reign of Emperor Kangxi (1661–1722), a period marked by peace and cultural consolidation. Originating from the Manchu people of Ulla in Northeast China, the embroidery was a meticulously crafted the court art form, symbolising hierarchical rank, authority, and social order. The designs embedded within these textiles reflected a codified visual language unique to the Manchu imperial court. However, efforts to preserve and interpret this heritage are facing challenges due to generational misunderstandings and historical misrepresentations by the public. This research aims to clarify the original meanings and hierarchical structure of Manchu embroidery, with the broader objective of informing its integration into contemporary Chinese fashion. Using a descriptive method, the study triangulates data from observations, visual archives, and museum collections. Semiotic theory is applied to decode the symbolic meanings of the motifs, while structuralist theory, particularly Lévi-Strauss’s and Binary Opposition are used to analyse the underlying systems and meaning that associate specific motifs with social rank. The findings offer valuable insights for both academic discourse and practical motifs application in fashion design, contributing to the preservation and revitalisation of Manchu textile heritage in contemporary contexts. ABSTRAK Kajian ini meneroka kepentingan sejarah dan budaya Sulaman Diraja Manchu yang berkembang semasa Dinasti Qing (1636–1912), terutamanya di bawah pemerintahan Maharaja Kangxi (1661–1722), iaitu satu era yang dikenali dengan kestabilan dan pengukuhan budaya. Sulaman ini berasal dari masyarakat Manchu di Ulla, Timur Laut China merupakan hasil seni istana yang dihasilkan dengan teliti, berfungsi sebagai lambang hierarki, kuasa, dan status sosial. Corak-corak yang dihasilkan pada sulaman ini mencerminkan sebuah bahasa visual yang tersusun dan unik khusus untuk golongan bangsawan di Manchu. Namun, usaha pemeliharaan dan pentafsiran motif warisan ini menghadapi cabaran akibat kurangnya kefahaman generasi masa kini serta ketidak-tepatan dalam mentafsir maklumat sejarah yang berkaitan. Kajian ini bertujuan menjelaskan makna asal serta struktur hierarki dalam sulaman Manchu, dengan objektif untuk menyokong pengaplikasian sulaman Manchu ke dalam fesyen kontemporari di China. Melalui metodologi deskriptif, kajian ini menggunakan teknik analisis data triangulasi dengan menggabungkan data daripada pemerhatian, arkib, dokumentasi visual dan koleksi muzium. Teori semiotik digunakan untuk mentafsir makna simbolik motif-motif sulaman Manchu manakala teori strukturalisme, terutamanya kerangka Lévi-Strauss dan Binary Opposistion digunakan untuk menganalisis sistem pengkelasan motif yang menghubungkan motif tertentu dengan status sosial. Dapatan kajian ini menawarkan cadangan praktikal untuk mengaplikasikan motif tradisional dari sulaman dinasti Mancu dalam produk kontemporari. Ia sekaligus menyumbang kepada usaha pemuliharaan dan menghidupkan semula warisan tekstil Manchu dalam konteks kontemporari.